Ta có điều kiện \(\hept{\begin{cases}y\ge-6\\x\ge-6\\x+y\ge0\end{cases}}\)
Theo đề bài thì: \(x+y=\sqrt{x+6}+\sqrt{y+6}\)
\(\Leftrightarrow\left(x+y\right)^2=\left(\sqrt{x+6}+\sqrt{y+6}\right)^2\)
\(\Leftrightarrow P^2\le\left(1^2+1^2\right)\left(x+y+12\right)\)
\(\Leftrightarrow P^2-2P-24\ge0\)
\(\Leftrightarrow-4\le P\le6\)
\(\Leftrightarrow-4< P\le6\left(1\right)\)
Ta lại có:
\(\Leftrightarrow\left(x+y\right)^2=\left(\sqrt{x+6}+\sqrt{y+6}\right)^2\)
\(\Leftrightarrow P^2=x+y+12+2\sqrt{\left(x+6\right)\left(y+6\right)}\)
\(\Leftrightarrow P^2-P-12=2\sqrt{\left(x+6\right)\left(y+6\right)}\ge0\)
\(\Leftrightarrow\left(P+3\right)\left(P-4\right)\ge0\)
\(\Leftrightarrow\orbr{\begin{cases}P\le-3\left(l\right)\\P\ge4\left(2\right)\end{cases}}\)
Từ (1) và (2) \(\Rightarrow4\le P\le6\)
Vậy GTNN là \(P=4\)đạt được khi \(\hept{\begin{cases}x=-6\\y=10\end{cases}}or\hept{\begin{cases}x=10\\y=-6\end{cases}}\)
GTLN là \(P=6\) đạt được khi \(x=y=3\)
Nhầm dấu 1 chỗ. Sửa lại nhé
Ta có điều kiện \(\hept{\begin{cases}y\ge-6\\x\ge-6\\x+y\ge0\end{cases}}\)
Theo đề bài thì: \(x+y=\sqrt{x+6}+\sqrt{y+6}\)
\(\Leftrightarrow\left(x+y\right)^2=\left(\sqrt{x+6}+\sqrt{y+6}\right)^2\)
\(\Leftrightarrow P^2\le\left(1^2+1^2\right)\left(x+y+12\right)\)
\(\Leftrightarrow P^2-2P-24\le0\)
\(\Leftrightarrow-4\le P\le6\)
\(\Leftrightarrow-4< P\le6\left(1\right)\)
Ta lại có:
\(\Leftrightarrow\left(x+y\right)^2=\left(\sqrt{x+6}+\sqrt{y+6}\right)^2\)
\(\Leftrightarrow P^2=x+y+12+2\sqrt{\left(x+6\right)\left(y+6\right)}\)
\(\Leftrightarrow P^2-P-12=2\sqrt{\left(x+6\right)\left(y+6\right)}\ge0\)
\(\Leftrightarrow\left(P+3\right)\left(P-4\right)\ge0\)
\(\Leftrightarrow\orbr{\begin{cases}P\le-3\left(l\right)\\P\ge4\left(2\right)\end{cases}}\)
Từ (1) và (2) \(\Rightarrow4\le P\le6\)
Vậy GTNN là \(P=4\)đạt được khi \(\hept{\begin{cases}x=-6\\y=10\end{cases}}or\hept{\begin{cases}x=10\\y=-6\end{cases}}\)
GTLN là \(P=6\) đạt được khi \(x=y=3\)